Pandangan Akuntansi Sektor Publik Dalam Q.S Al-Ahzab Ayat 23 - Fadyah Azzarah Oktaviani; Elicia Nabilah; Mohamad Djasuli (IAIN Madura, 2023)
This article aims to describe the views of public sector accounting in Q.S Al-Ahzab Verse 23. In this article, the author tries to describe how accountants behave professionally in carrying out their profession and dealing with situations according to Q.S Al-Ahzab verse 23. Next, the author explains the behavior accountants in the context of Islamic work ethics such as honesty, fairness, and truth. In the context of honesty ethics, accountants are required to be open and candid, fulfill agreements, and refuse all kinds of gifts of unknown origin. The behavior of accountants in the perspective of truth is shown by always using rules as a basis for acting and behaving. In the context of ethical justice, accountants do not discriminate against the treatment given to clients and distribute the rights of clients as a whole.